Distant sisters : Australasian women and the international struggle for the vote, 1880-1914 - Keating, James (Ph. D. in history) (Gender in history., 2020)
Distant sisters offers a new history of the connections women in Australia and New Zealand made with one another, and the rest of the world, first in their pioneer pursuit of the vote and then in their struggle to sell its merits overseas. Although the Australasian suffrage campaigns occurred side-by-side and shared a commitment to international outreach, this book is the first to take these parallels seriously. Recovering a forgotten regional suffrage history, it uses their stories to explore the rise of suffrage internationalism in the late nineteenth century and, importantly, to chart its political, geographic, and racial limits. Covering the period 1880-1914, the book charts the development of an international consciousness among elite and ordinary suffragists alike. Following the conduits that allowed them to think and act across borders, it shows how Australasian suffragists positioned themselves within the emerging international women's movement and shaped organisations like the International Woman Suffrage Alliance and World's Woman's Christian Temperance Union. Distant Sisters simultaneously unveils the intimate dimensions of internationalism, showing how sentiments ignited by the exchange of letters, newspapers and photographs, and preserved in scrapbooks, briefly led the Australasian suffragists to grace British and American concert halls. While often fraught and frustrating, their attempts to forge meaningful intercolonial and international connections complicate both insular national histories of suffrage and the orthodox Euro-American narrative of fin-de-siecle feminist internationalism. Written in an approachable, case-study driven style, this book will appeal to undergraduates and academic specialists in the fields of feminist history, British imperial history and Australian and New Zealand studies alike.